Representasi Maskulinitas dalam Film 27 Steps of May - SAFIRA, HERVINA VIDYA (Universitas Negeri Surabaya, 2020)
27 Steps of May ia a film that inspired by the tragedy of mass raped in 1998. Tells story of the lives of rape victim eight years after the incident, this film is show how patriarchy culture portrays masculinity in Indonesia. Masculinity is the concept of how men should be men in social life. This film shows that rape is the result of hegemonic masculinity which assumes that men must be the dominant party taht capable of controlling women. in addition, masculinity also creates silence of rape victims. Masculinity also requires men to be able to protect women, which ultimately makes men described as helpers and defenders of rights. Using Roland Barthes's semiotics research method, it is known that 27 Steps of May is represent traditional masculinity and modern masculinity through the characters in it. Roland Barthes's semiotics was chosen because it is able to provide depth of meaning by using denotation, connotation and myth. Keywords: representation, masculinity, sexual harassment